THE ROLE OF THE MUZAKARAH METHOD IN IMPROVING STUDENTS COMPETENCE IN UNDERSTANDING THE YELLOW BOOK AT SUBULUSSALAM SIMPANG EMPAT ISLAMIC BOARDING SCHOOL - Al Ichsan, Rofa; Kardi, Juliwis; Iswandi, Iswandi; Hidayat, Taufik (Amanah Publishing, 2026)
This research is motivated by the book review activity at the Subulus Salam Islamic Boarding School, which focuses on students at the Islamic Senior High School (Madrasah Aliyah) to improve their understanding of the yellow book through interactive discussions. Although beneficial, this activity still faces obstacles such as limited Arabic language skills, differences in student backgrounds, and low active participation, so a more in-depth study of the method's effectiveness is needed. This study aims to describe the role of the book review method in improving students' competence in reading, interpreting, and discussing books; analyze students' motivation in participating in the book review; and identify supporting and inhibiting factors for the activity. Using a descriptive qualitative method through a field research approach, data were collected through observation, interviews, and direct interaction with informants to understand the phenomenon holistically. The results show that the book review method helps improve reading, interpreting, and discussing skills more confidently, despite the large number of participants and varying abilities. The level of student activity has been shown to have a significant impact on understanding; the more active they are in reading, asking questions, and discussing, the deeper their understanding. The success of muzakarah is supported by a passion for learning, a religious environment, a regular schedule, communicative facilitators, and adequate facilities. However, obstacles remain, such as fatigue, lack of preparation, differences in language skills, and technical factors. Suggested solutions include small group formation, additional mentoring, task rotation, motivation, and improved facilities and time management so that all students can optimally benefit from muzakarah activities.